Effects of combined resistance training and weightlifting on motor skill performance of adolescent male athletes - Pichardo, W. A.; Oliver, L. J.; Harrison, B. C.; Maulder, S. P.; Lloyd, S. R.; Kandoi, R. (The Journal of Strength and Conditioning Research, 2019)
Resistance training and weightlifting are regarded as safe and effective training methods for youth. However, no studies have examined the effects of a year-long resistance training program using weightlifting movements on strength, speed, or power. Therefore, the purpose of this study was to determine the long-term effects of combined resistance training (traditional strength training + plyometrics) with or without weightlifting movements on motor skill performance of adolescent males. Fifty-nine males aged 12-14 years were matched by maturity and allocated to a combined resistance training or a combined resistance training with weightlifting group. Each group completed 28 total weeks of training over an academic year. Pre-, mid- (14 weeks of training), and post-training (28 weeks of training) tests included the resistance training skills battery quotient (RTSQ), absolute isometric midthigh pull peak force (IMTPABS) and ratio-scaled isometric midthigh pull peak force (IMTPREL), countermovement jump, horizontal jump, and 10-, 20-, and 30-m sprint. Repeated-measure analysis of variance revealed that there were no significant between-group responses, but all variables improved significantly within-group. Both groups made small-moderate improvements in RTSQ, IMTPABS, and IMTPREL after the first 14 training weeks (d = 0.45-0.86), whereas small-moderate improvements in lower body power, upper body power, and speed were made after the second 14 training weeks (d = 0.30-0.95). Both groups made small-moderate improvements in all performance variables after 28 weeks of training. These findings highlight the importance of establishing movement competency and strength as a foundation for the subsequent development of power. Furthermore, these findings may help practitioners understand the time course of certain adaptations following a long-term periodized plan for adolescent males.